CADAR, MEDIA, DAN IDENTITAS PEREMPUAN MUSLIM - Ratri, Lintang (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract :Although Indonesia is one of the biggest Moslem country in the world, 'veiled woman' are still become sensitive issue to be discussed.Woman Moslem who decided to wear veil face many consequences since she should follow more intense learning process about the nature of women. They alsoare associated as fanatic Moslem organization. This representation is getting stronger after media labeling them as â€œterrorist's wifeâ€.The fact show that veiled women have Â strong character since they survive around people including Moslem who see them as 'otherness'. However, based on author' observation, veiled woman never experience awkwardness communication with community. They socialize (ukuwahIslamiah) with all Moslem including woman Moslem who do not wear headscarves or veil. They against terrorism as the concept of jihad (Moslem' struggle against'enemies'). They believe that jihad can be done by many other activities such us working, learning and maintaining passions.Therefore, they say that the stigma of 'veiled women is terrorist's wife' is merely the mass media constructions. Thus, they suggest for all veiled women to continue to fight for a position as a woman, as well as defend against the discrimination against their choice to wear veil.Keywords : Vailed Woman, Social Representationpermalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3155